Pengklasifikasian Item Persediaan Menggunakan Metode Always Better Control-Fuzzy - Retno Octaviyani; Desi Yuniarti; Yuki Novia Nasution (Program Studi Statistika FMIPA Universitas Mulawarman, 2018)
ABC Classification is a method of controlling inventory to control a small quantity of goods but has a high usage value. Inventories are categorized into three classes, namely A, B, and C. Fuzzy classification is a classification used to classify training data sets (data sets used to generate membership functions) and to predict data testing. The purpose of this study was to control inventory using the ABC classification method, Fuzzy Classification, and ABC-fuzzy classification. The results of ABC classification showed that from 182 items of drug, class A is consisted of 15 items of drug with a value of 69,276% usage, class B is consisted of 34 items of drug with a value of use of 20.723%, and class C is consisted of 133 items of drug with value use of 10.010%. The results of the fuzzy classification showed that of the 182 drug items, fuzzy 3 consisted of 9 medicinal items which meant that, there were 9 very important drugs, fuzzy 2 consisted of 171 drug items which meant that there were 171 important medicines, and fuzzy 1 consisted of 2 items of medicine which means that, there are 2 less important drugs. The results of the ABC-fuzzy classification showed that of 182 drug items, there were 17 items of drugs in the first priority which means that the 17 items of this drug are most preferred, then there are 41 items of drug on the 2nd priority which means the stock of 41 items of this drug is preferred, 124 items of drug on priority 3 which means that 124 items of this drug is not preferred.